Participation of heart mitochondria in myocardial protection against ischemia/reperfusion injury: benefit effects of short-term adaptation processes - Ferko, M; Kancirová, I; Jašová, M; Waczulíková, I; Čarnická, S; Kucharská, J; Uličná, O; Vančová, O; Muráriková, M; Ravingerová, T; Ziegelhöffer, A (Physiological research, 2015)
Acute streptozotocin diabetes mellitus (DM) as well as remote ischemic preconditioning (RPC) has shown a favorable effect on the postischemic-reperfusion function of the myocardium. Cardioprotective mechanisms offered by these experimental models involve the mitochondria with the changes in functional properties of membrane as the end-effector. The aim was to find out whether separate effects of RPC and DM would stimulate the mechanisms of cardioprotection to a maximal level or whether RPC and DM conditions would cooperate in stimulation of cardioprotection. Experiments were performed on male Wistar rats divided into groups: control, DM, RPC and DM treated by RPC (RPC+DM). RPC protocol of 3 cycles of 5-min hind limb ischemia followed by 5-min reperfusion was used. Ischemic-reperfusion injury was induced by 30-min ischemia followed by 40-min reperfusion of the hearts in Langendorff mode. Mitochondria were isolated by differential centrifugation, infarct size assessed by staining with 1 % 2,3,5-triphenyltetrazolium chloride, mitochondrial membrane fluidity with a fluorescent probe DPH, CoQ(9) and CoQ(10) with HPLC. Results revealed that RPC as well as DM decreased the infarct size and preserved mitochondrial function by increasing the mitochondrial membrane fluidity. Both used models separately offered a sufficient protection against ischemic-reperfusion injury without an additive effect of their combination.
Keywords: streptozocin; přivykání k ischémii; Animals; experimentální diabetes mellitus; srdeční mitochondrie; Regional Blood Flow; Myocardial Reperfusion Injury; Hindlimb; Rats, Wistar; Mitochondria, Heart; Time Factors; časové faktory; fyziologická adaptace; mitochondriální membrány; reperfuzní poškození myokardu; fluidita membrány; Membrane Fluidity; Ischemic Preconditioning; Isolated Heart Preparation; zadní končetina; Male; modely nemocí na zvířatech; Adaptation, Physiological; Disease Models, Animal; regionální krevní průtok; Myocardial Infarction; Mitochondrial Membranes; Streptozocin; zvířata; mužské pohlaví; preparace izolovaného srdce; Myocardium; myokard; infarkt myokardu; potkani Wistar; Diabetes Mellitus, Experimental